Return to training after coronavirus (SARS-CoV-2/COVID-19) infection - I. E Zelenkova; D. S. Ilyin; V. A. Badtieva (Спортивная медицина: наука и практика, 2020)
The coronavirus pandemic raises an important issue of the return professional and amateur athletes to training after COVID-19 infection. Since no standard protocols for return to sports after the new coronavirus infection are approved to date, and few studies were done on SARS-CoV-2 infection short- and long-term complications in sports professionals, the question arises about the criteria for the athletes’ training restart after COVID-19 infection to protect the health of athletes and prevent long-term adverse health effects. This review is a synthesis of currently available information on the athletes’ re-involvement into the training process after COVID-19 infection.